An adaptive replacement of the rule update triggers the cooperative evolution in the Hawk–Dove game. (April 2019) - Sakiyama, Tomoko; Arizono, Ikuo
Highlights: In this paper, we developed a novel spatial HD model replacing the best takes over update rule with different one. We investigated the effect of modifying update rules on the problem of cooperators extinction in the space HD games. We found that our model generated characteristic population patterns and represented the survival of cooperators compared with the classical spatial HD model in which the updated rule was fixed. Abstract: Since Maynard Smith and Price proposed the earliest version of Hawk–Dove (HD) game, it attracted researchers' attention as one of models of conflict for two players in game theory. In conflict game, the players' benefit depends on the strategy of opponent for each other. In the classical spatial HD games, if one player adopts defector strategy, it tends to get high payoffs, and therefore increases population of the same strategy, which resulting in an extinction of cooperators. Several studies tried to solve the problem of an extinction of cooperator in spatial HD game. In this paper, we developed a novel spatial HD model replacing the best takes over update rule with different one, and investigated the effect of modifying update rules on the problem of collaborators extinction in space HD games. We found that our model generated characteristic population patterns and represented the survival of cooperators compared with the classical spatial HD model in which the updated rule was fixed.